Structural elucidation of fucosylated chondroitin sulfates from sea cucumber using FTICR-MS/MS. Issue 1 (February 2018) - Agyekum, Isaac; Pepi, Lauren; Yu, Yanlei; Li, Junhui; Yan, Lufeng; Linhardt, Robert J; Chen, Shiguo; Amster, I Jonathan
Fucosylated chondroitin sulfates are complex polysaccharides extracted from sea cucumber. They have been extensively studied for their anticoagulant properties and have been implicated in other biological activities. While nuclear magnetic resonance spectroscopy has been used to extensively characterize fucosylated chondroitin sulfate oligomers, we herein report the first detailed mass characterization of fucosylated chondroitin sulfate using high-resolution Fourier transform ion cyclotron resonance mass spectrometry. The two species of fucosylated chondroitin sulfates considered for this work include Pearsonothuria graeffei (FCS-Pg) and Isostichopus badionotus (FCS-Ib). Fucosylated chondroitin sulfate oligosaccharides were prepared by N -deacetylation–deaminative cleavage of the two fucosylated chondroitin sulfates and purified by repeated gel filtration. Accurate mass measurements obtained from electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry measurements confirmed the oligomeric nature of these two fucosylated chondroitin sulfate oligosaccharides with each trisaccharide repeating unit averaging four sulfates per trisaccharide. Collision-induced dissociation of efficiently deprotonated molecular ions through Na/H + exchange proved useful in providing structurally relevant glycosidic and cross-ring product ions, capable of assigning the sulfate modifications on the fucosylated chondroitin sulfate oligomers. Careful examination of the tandem mass spectrometry of both species deferring in the positions of sulfate groups on the fucose residue (FCS-Pg-3, 4- O S) and (FCS-Ib-2, 4- O S) revealed cross-ring products 0, 2 Aαf and 2, 4 X2αf which were diagnostic for (FCS-Pg-3, 4- O S) and 0, 2 X2αf diagnostic for (FCS-Ib-2, 4- O S). Mass spectrometry and tandem mass spectrometry data acquired for both species varying in oligomer length (dp3–dp15) are presented.